STUDY ON CHALLENGES AFFECTING WOMEN ENTREPRENEURS’ BUSINESS SUCCESS IN ADEN, YEMEN - AHMED NASSER, RANA GALAL; HASIM, MUHAMMAD ASYRAF (Research in Management of Technology and Business, 2023)
This study aimed to investigate the challenges impacting the business success of women entrepreneurs in Aden, Yemen. The research employed a primary data approach, utilizing a well-structured questionnaire to collect quantitative data. The focus of the study was to examine three key factors, which were identified through a literature review and found that these factors significantly influence the success of entrepreneurs. These factors encompassed financial support, family support, and knowledge. Descriptive frequency, normality, and correlation analyses were conducted to address the research objectives. A reliability test was also carried out on the questionnaire variables to ensure internal consistency and data quality. The correlation analysis results demonstrated noteworthy findings. Among the three identified factors, there was a significant positive correlation between women entrepreneurs’ business success and financial support. A substantial correlation was observed between women entrepreneurs’ business success and family support. The results of this study show a positive relationship between women entrepreneurs’ business success and knowledge. Based on the study’s results, the solution suggested is to enhance access to financial services, such as bank loans, and implement By doing so, it is anticipated that the overall business environment for women entrepreneurs in Aden would be significantly improved, leading to enhanced business success and economic growth in the region.